Radio active - O'Shaughnessy, William (Whitney Global Media Publishing Group, 2019)
This book is the author's fifth collection of essays, on-air interviews, tributes and eulogies, endorsements, recollections of an evening, and more from a broadcaster whose commentaries are akin to "potato chips," per former Secretary of State Kissinger, because "you can't stop with only one." The book opens with a defense of the First Amendment and collected correspondence with "heroes" and "villains," and sections honoring former New York Governor Mario Cuomo, who said, "When [the author] is on his game ... he's better than anyone on the air or in print." There is also a section on the estimable Bush family. In eliciting revelations from his own circle, this compendium pulses with a life-affirming reverence for luminous people, places, and events, past and present